2006
DOI: 10.4049/jimmunol.176.9.5577
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II-Induced Mononuclear Leukocyte Interactions with Arteriolar and Venular Endothelium Are Mediated by the Release of Different CC Chemokines

Abstract: Angiotensin II (Ang-II) is associated with atherogenesis and arterial subendothelial mononuclear leukocyte infiltration. We have demonstrated that Ang-II causes the initial attachment of mononuclear cells to the arteriolar endothelium. We now report on the contribution of CC chemokines to this response. Intraperitoneal administration of 1 nM Ang-II induced MCP-1, RANTES, and MIP-1α generation, maximal at 4 h, followed by mononuclear leukocyte recruitment at 8 and 24 h. Using intravital microscopy within the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
76
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 45 publications
9
76
0
2
Order By: Relevance
“…2 for review). Consistent with the latter finding, blockade of AT 1 , the major receptor mediating the inflammatory actions of Ang II, reduces neutrophil recruitment and cytokine release in models of inflammation (12,37,38). However, to our knowledge, the expression of Mas receptor in periarticular tissues was demonstrated for the first time in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…2 for review). Consistent with the latter finding, blockade of AT 1 , the major receptor mediating the inflammatory actions of Ang II, reduces neutrophil recruitment and cytokine release in models of inflammation (12,37,38). However, to our knowledge, the expression of Mas receptor in periarticular tissues was demonstrated for the first time in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to inhibiting neutrophil influx due to the inhibition of local production of chemokines, it was possible that Mas agonists could be directly interfering with the process of leukocyte-endothelial cell interaction, hence preventing their influx. In support of the latter possibility, other studies have found that Ang II via AT 1 receptor stimulated leukocyte-endothelium interactions and increased neutrophil migration in vivo (37,38). In our study, treatment with the Mas receptor agonist AVE 0991 significantly inhibited rolling and cell adhesion of leukocytes to endothelial cells in the joint microvasculature of mice subjected to AIA.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The reninangiotensin system (RAS) may play a role in this activation process since hypercholesterolemia upregulates AT 1 receptor expression in a variety of tissues 2 and in vitro stimulation of AT 1 subtype receptors by angiotensin (Ang) II directly increases monocyte CD11b. 3 The suppression of monocyte CD11b by AT 1 receptor blockade in patients with coronary artery disease 4 and in monkeys with hypercholesterolemia-induced atherosclerosis 5 provides additional evidence that the RAS regulates the phenotype of circulating monocytes and their atherogenicity. The anti-inflammatory action of Ang II receptor blockers (ARBs) reflected by diminished CD11b expression may be an important mechanism by which this drug class exerts its anti-atherosclerotic effects independent of blood pressure-lowering.…”
Section: Introductionmentioning
confidence: 99%
“…Angiotensin II induces endothelial dysfunction and vascular remodeling in several experimental models [12], and is known to promote both mitogenic signals and oxidative stress in the vasculature [13]. These signals result in arterial inflammation, which in turn upregulates monocyte recruitment [11,[14][15][16]. However, it remains unclear, whether inhibition of angiotensin II reduces monocyte adhesion to endothelial cells beyond the effect of simply reducing blood pressure.…”
mentioning
confidence: 99%